La metodología 9s para mejorar la gestión administrativa en la Institución Educativa Abelardo Manuel Gamarra Rondo, Sarín, Sánchez Carrión, 2018 - Julca Asto, Maria Jesus Marlene (2020)
This research, applicative and pre experimental was conducted in order to determine whether the application of the methodology 9s could improve administrative management in the Educational Institution Manuel Abelardo Gamarra Rondo, Sarin, Sanchez Carrion, 2018._x000D_ The sample population consisted of 34 people from the Educational Institution Manuel Abelardo Gamarra Rondo, sarin, Sánchez Carrión, 2018, hiring the hypothesis was made with the classic pre - experimental design with pretest and posttest applied to the experimental group._x000D_ The methodology was applied 9s considering two related units classification, organization, cleanliness, personal, discipline, perseverance, commitment, coordination and standardization. It lasted eight weeks during which a total of 32 hours of class, distributed in 12 sessions were developed._x000D_ The posttest were applied one week after completion of the development of the methodology the 9s, with the data obtained from the application of the instrument, charts and graphs statistical built subsequently made use of the test "Z" for checking averages._x000D_ In the posttest significant improvement of administrative management, it appreciated by the Educational Institution with 0.57 confidence._x000D_ The validity of the results was checked with the test "Z" which gave a value of p <0.05, indicating that the application of the methodology 9s significantly improved the management of Educational Institution Manuel Abelardo Gamarra Rondo, Sarin, Sánchez Carrión, 2018